The changing contribution of forests to livelihoods: evidence from Daxi Village, Zhejiang Province, China - Gutiérrez Rodríguez, L.; Ruíz Pérez, M.; Yang, Xiaosheng; Fu, Maoyi; Geriletu; Wu, D. (2009)
There are positive and negative feed-back links between forestry and poverty. The role of forests as part of a rural development strategy is much debated in literature. We have explored this role and links for a montane forest village in East China using official historical data and our own field survey of 92 households. The opportunities that forest resources have offered to farmers at different stages of socio-economic development are identified. The changes in farmers' livelihood strategies caused by using forest products and the associated increase of inequalities are assessed. Forest management has been gradually shifting from a focus on forest production centred on bamboo to a multipurpose orientation in which conservation to promote tourism has become increasingly important. While bamboo still remains the main income equaliser factor, different forest products add to the portfolio of opportunities of upper and lower income farmers as they move along their development ladders.